Replication-directed sister chromosome alignment in Escherichia coli. - Liu, X; Wang, X; Reyes-Lamothe, R; Sherratt, D (2010)
Non-replicating Escherichia coli chromosomes are organized as sausage-shaped structures with the left (L) and the right (R) chromosome arms (replichores) on opposite cell halves and the replication origin (oriC) close to midcell. The replication termination region (ter) therefore passes between the two outer edges of the nucleoid. Four alignment patterns of the two <lr> sister chromosomes within a cell have been detected in an asynchronous population, with the <lrlr> pattern predominating. We test the hypothesis that the minority <lrrl> and <rllr> patterns arise because of pausing of DNA replication on the right and left replichores respectively. The data resulting from transient pausing or longer-term site-specific blocking of replication show that paused/blocked loci remain close to midcell and the normally replicated-segregated loci locate to the outer regions of the nucleoid, therefore providing experimental support for a direct mechanistic link between DNA replication and chromosome organization.</rllr></lrrl></lrlr></lr>